2022
DOI: 10.1038/s41540-022-00217-w
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory receptors contribute to progression of kidney fibrosis

Abstract: Olfactory receptors (ORs) which are mainly known as odor-sensors in the olfactory epithelium are shown to be expressed in several non-sensory tissues. Despite the specified role of some of these receptors in normal physiology of the kidney, little is known about their potential effect in renal disorders. In this study, using the holistic view of systems biology, it was determined that ORs are significantly changed during the progression of kidney fibrosis. For further validation, common differentially expresse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Furthermore, Pluznick et al determined that Olfr78 regulates blood pressure by interacting with byproducts of gut microbiota ( Pluznick et al, 2013 ). Moreover, a recent study by Motahharynia et al revealed that olfactory receptors contribute to the progression of kidney fibrosis ( Motahharynia et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Pluznick et al determined that Olfr78 regulates blood pressure by interacting with byproducts of gut microbiota ( Pluznick et al, 2013 ). Moreover, a recent study by Motahharynia et al revealed that olfactory receptors contribute to the progression of kidney fibrosis ( Motahharynia et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“… 30 The little we know is that ORs significantly change during the progression of kidney fibrosis. 31 …”
Section: Discussionmentioning
confidence: 99%
“…While the participation of renal OR signaling in the pathophysiology of kidney diseases has not yet been established, a few studies have pointed out a correlation between altered OR expression, the activation of pro-fibrotic pathways, and the development of renal fibrosis leading to CKD [108,109]. The formation of kidney stones, which is a risk factor for CKD, has also been associated with dysregulated expression of several ORs in the renal papillary tips [110,111].…”
Section: Regulation Of Fibrosis and Kidney Stone Formationmentioning
confidence: 99%